(untitled) (Dhaka University Journal of Biological Sciences, 2019)
Good self-esteem and coping skills are essential to maintain a strong, happy and healthy life. The present study examined the self-esteem and coping skills of victims and non-victims of bullying in public school. The sample consisted of 150 participants (75 bullied and 75 non-bullied) who were selected through convenience sampling technique from different public schools of Dhaka city. The Bangla version of the California bullying victimization scale, the Rosenberg’s self-esteem scale and the coping scale were used to achieve the research objectives. Result of the study showed that bullying was negatively correlated with self-esteem and coping skills whereas self-esteem was positively correlated with coping skills. Result also showed that there were significant differences in self-esteem and in coping skills between victims and non-victims of bullying. The findings of the present study will advance our understanding about the negative impact of bullying on children’s mental health and will help mental health professionals to develop bullying awareness program for teachers and parents. Dhaka Univ. J. Biol. Sci. 28(2): 139-146, 2019 (July)